What drives diversification of national food supplies? A cross-country analysis - Choudhury, Samira; Headey, Derek D. (International Food Policy Research Institute, 2016)
Although the diversification of national food supplies (DFS) is a necessary (but not sufficient) condition for the diversification of diets and for reductions in undernutrition in poor countries, little previous research has analyzed how DFS varies across countries and regions, how rapidly it has changed over time, and what economic, social, and agroecological factors may be driving these observed patterns and trends in DFS. The study addresses those questions through a cross-country analysis. We first review economic theory and evidence on the diversification of production and diets in developing countries, particularly the importance of economic growth and other structural transformation processes, as well as the scope for agroecological factors to shape consumption outcomes in the presence of market imperfections, such as high transport costs. We then construct and analyze a rich cross-country dataset linking a simple DFS indicator—the share of calories supplied by nonstaple foods—with a wide range of economic, social, infrastructural, and agroecological indicators. Descriptive evidence and regression analyses show that several indicators of structural transformation (economic growth, urbanization, and demographic change) are strong predictors of DFS within countries. However, the results also suggest that time-invariant agroecological factors are significantly associated with DFS, such that some countries have exceptionally low or high DFS relative to their level of economic development. We discuss the implications of these findings for food and nutrition strategies, particularly the challenge of accelerating dietary diversification in the absence of sustained and very rapid economic growth and structural transformation, especially in countries where agroecological conditions additionally hinder access to a more diverse food basket.